Early Elevation of Monocytic-to-Polymorphonuclear Myeloid-Derived Suppressor Cells Ratio in Critical Illness is Associated with Favorable Clinical Outcomes - Jia L; Long L; Wang H; Ge C; Zhang Z; Zhang Z; Zhao H (Journal of Inflammation Research, 2025)
Lijing Jia, Ling Long, Huawei Wang, Chen Ge, Ze Zhang, Zhiyang Zhang, Heling Zhao Department of Intensive Care Medicine, Hebei General Hospital, Shijiazhuang, People’s Republic of ChinaCorrespondence: Heling Zhao, Email 90030201@hebmu.edu.cnBackground: Myeloid-derived suppressor cells (MDSCs), comprising polymorphonuclear (PMN-MDSCs) and monocytic subsets (M-MDSCs), are immunosuppressive immature myeloid cells implicated in disease progression and prognosis across multiple pathologies.Purpose: To investigate the clinical significance of early MDSCs subset expansion in critical illness and identify novel prognostic biomarkers for risk stratification.Patients and Methods: This prospective study enrolled 85 critically ill adults (APACHE II ≥ 15), stratified into survivors (n=47) and non-survivors (n=38). MDSCs subsets were quantified via flow cytometry. Concurrent measurements included lactate, IL-6, CRP, lymphocyte subsets, and Tregs. Primary outcomes were 28-day all-cause mortality and secondary infection rates.Results: Survivors exhibited significantly higher M-MDSCs% (median [IQR]: 4.824 [1.863– 9.776] vs 2.503 [1.480– 5.224], P< 0.05) and elevated M-MDSCs/PMN-MDSCs ratios (122.166 [34.220– 307.500] vs 28.324 [5.042– 88.128], P< 0.01). Patients with M-MDSCs/PMN-MDSCs ratios ≥ 85.765 demonstrated markedly lower mortality (23.08% vs 59.19%; hazard ratio [HR] = 3.530, 95% confidence interval [CI]: 1.668– 7.467, P< 0.001), with the low-ratio group exhibiting a 2.56-fold higher mortality risk. A combined stratification model (M-MDSCs/PMN-MDSCs + APACHE II score) revealed a 7.48-fold increase in mortality in the low-ratio/high-APACHE II subgroup compared to the high-ratio/low-APACHE II subgroup (86.36% vs 11.54%, P< 0.001).Conclusion: Elevated levels of M-MDSCs in the early stages of critical illness may exert protective effects. The ratio of M-MDSCs/PMN-MDSCs demonstrates predictive value for 28-day mortality, positioning it as a potential biomarker for prognostic assessment, but further multicenter studies are still needed to validate it.Keywords: myeloid-derived suppressor cells, critically ill, prognosis